2006
DOI: 10.1111/j.1365-2141.2006.06223.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood stem cell yield in 400 normal donors mobilised with granulocyte colony‐stimulating factor (G‐CSF): impact of age, sex, donor weight and type of G‐CSF used

Abstract: SummaryMobilised peripheral blood is now the main source of stem cells collected from normal donors. We report our experience of mobilising and collecting 400 normal healthy donors using standardised procedures and techniques. Target recipient doses were reached with one aphaeresis in 63% of donors and with two aphereses in 81% of donors. Approximately 2% of donors yielded such low progenitor values that they were termed 'poor mobilisers'. There were minor effects of donor age, weight and sex and where possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
116
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 40 publications
16
116
3
Order By: Relevance
“…Pulsipher and colleagues reported that among 2,408 unrelated donors of PBSCs, two-thirds (66%) underwent two apheresis procedures, whereas the remaining donors completed their donations in a single day (19). Ings and colleagues reported that among 400 unrelated donors of PBSCs target recipient doses were reached with one aphaeresis in 63% of donors and with two apheresis in 81% of donors; 19% of the donors needed more than two apheresis (20). AMD3100 (plerixafor, Mozobil) is a reversible direct antagonist of the interaction between the chemokine SDF-1 and its receptor CXCR4 and is used for HSPC mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsipher and colleagues reported that among 2,408 unrelated donors of PBSCs, two-thirds (66%) underwent two apheresis procedures, whereas the remaining donors completed their donations in a single day (19). Ings and colleagues reported that among 400 unrelated donors of PBSCs target recipient doses were reached with one aphaeresis in 63% of donors and with two apheresis in 81% of donors; 19% of the donors needed more than two apheresis (20). AMD3100 (plerixafor, Mozobil) is a reversible direct antagonist of the interaction between the chemokine SDF-1 and its receptor CXCR4 and is used for HSPC mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…This study looked for differences in HPC mobilization in response to glycosylated Hu or nonglycosylated rHu G-CSF in patients with hematological tumors that are the most frequent candidates for auto-SCT and that require combined mobilization with chemotherapy and G-CSF. The appropriate schedule of mobilization in terms of type of chemotherapy, doses and timing of G-CSF administration has been discussed in several studies, 3,18,[21][22][23][24][25][26] whereas the role of G-CSF glycosylation is still not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the literature, mobilization and harvest of CD34 ϩ cells were significantly more effective in male than in female donors. [16][17][18] Future research could identify genetic factors that would predict which donors are likely to fail adequate mobilization. One could envision alternative mobilization regimens 19 or decide for bone marrow collection.…”
Section: Discussionmentioning
confidence: 99%